2005
DOI: 10.1029/2004gb002343
|View full text |Cite
|
Sign up to set email alerts
|

Controls on the seasonal exchange of CH3Br in temperate peatlands

Abstract: [1] Measurements of CH 3 Br exchange at two New Hampshire peatlands (Sallie's Fen and Angie's Bog) indicate that net flux from these ecosystems is the sum of competing production and consumption processes. Net CH 3 Br fluxes were highly variable and ranged from net emission to net uptake between locations within a single peatland. At Sallie's Fen, net CH 3 Br flux exhibited positive correlations with peat temperature and air temperature during all seasons sampled, but these relationships were not observed at A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2006
2006
2013
2013

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(27 citation statements)
references
References 36 publications
2
25
0
Order By: Relevance
“…[22] The picture that emerges from consideration of this study in Swedish high-latitude wetlands, and the studies in arctic Alaska [Rhew et al, 2007;Teh et al, 2009] and New Hampshire peatlands [White et al, 2005] (together with further data from wetlands and peatlands in Scotland) is of land-atmosphere CH 3 Br and CH 3 Cl fluxes in such systems being the net resultant of plant-and soil-mediated emission and soil-mediated uptake; and that the relative magnitudes of each varies with micro-topology of the site (i.e., with vegetation and hydrology) and with time during the season. The latter factor impacts on vegetation activity and hydrology.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[22] The picture that emerges from consideration of this study in Swedish high-latitude wetlands, and the studies in arctic Alaska [Rhew et al, 2007;Teh et al, 2009] and New Hampshire peatlands [White et al, 2005] (together with further data from wetlands and peatlands in Scotland) is of land-atmosphere CH 3 Br and CH 3 Cl fluxes in such systems being the net resultant of plant-and soil-mediated emission and soil-mediated uptake; and that the relative magnitudes of each varies with micro-topology of the site (i.e., with vegetation and hydrology) and with time during the season. The latter factor impacts on vegetation activity and hydrology.…”
Section: Discussionmentioning
confidence: 99%
“…[5] Seasonal and diurnal trends in CH 3 Br and CH 3 Cl fluxes from non-polar ecosystems have been reported in a number of studies [e.g., Redeker et al, 2000;Rhew et al, 2002;White et al, 2005;Drewer et al, 2006;Manley et al, 2006], but there has been no consistent evidence for external parameters driving CH 3 Br or CH 3 Cl fluxes across all ecosystem types; individual studies have suggested that light [Drewer et al, 2006], temperature [Rhew et al, 2000[Rhew et al, , 2002Redeker and Cicerone, 2004], or soil pore-water saturation [Redeker and Cicerone, 2004] may affect emissions. In arctic Alaskan tundra it was found that drained sites had greater rates of CH 3 Br and CH 3 Cl uptake than flooded sites in both coastal and inland areas [Rhew et al, 2007;Teh et al, 2009], with water table depth correlating most strongly with CH 3 Cl and CH 3 Br net uptake [Teh et al, 2009].…”
Section: Introductionmentioning
confidence: 99%
“…The Montreal Protocol has led to cuts in the anthropogenic production of methyl bromide and thus to a decrease of the atmospheric Br load (Montzka et al, 2003). However, CH 3 Br is also produced by a broad range of natural sources, such as macroalgae (Laturnus, 2001), salt marshes (Rhew et al, 2000), rice paddies (Redeker et al, 2000) and peatlands (White et al, 2005), amongst others. Ocean uptake and decomposition by atmospheric OH radicals are currently believed to greatly outweigh known sources.…”
Section: Introductionmentioning
confidence: 99%
“…Few data sets have sufficient temporal resolution to identify seasonal and diurnal trends in CH 3 X fluxes. Clear seasonal trends have been observed at Scottish saltmarshes [ Drewer et al ., ; Blei et al ., ], New Hampshire wetlands [ White et al ., ], and Californian rice paddies [ Redeker and Cicerone , ]. In the saltmarshes and rice paddies CH 3 Br emission rates broadly corresponded to seasonal trends in plant growth, air temperature and light intensity, indicative of a biologically‐mediated process.…”
Section: Introductionmentioning
confidence: 99%